Викинги: [сборник] / Мария Семенова - Семенова Мария Васильевна (АСТ, 2008)
Экземпляры: аб. (2008) / Инвентарный номер: 52001 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 30 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-445